Educational site as information and communication technology on the elderly with dementia (Research, Society and Development, 2021)
Objective: this paper aims to describe the educational website interactivity as information and communication technology for the elderly with dementia. Method: it is a study of the experience report type, with a qualitative descriptive approach, developed through the extension project that has been taking place since 2011 at the School of Nursing with the support and integration of the Dean of Extension of Federal Fluminense University. Results: this site as an educational technology provides dissemination and interactivity on guidance about elderly people with dementia and their caregivers, integrating support for families and caregivers of elderly people with dementia in times of the Covid-19 Pandemic. Final considerations: this educational site as information and communication technology for the elderly with dementia is a tool that allows for information and exchange of knowledge, aimed at family members and caregivers.